The Fundamentals of Health Research training for community health workers: a mixed-methods study - Wolfe, Nicole; Diaz, Andrea; Do-Golden, Brian; Karpilow, Esther; Rubio-Diaz, Mayra; Kipke, Michele D. (Frontiers in Public Health, 2025)
IntroductionCommunity Health Workers/Promotores de Salud (CHW/Ps) are trusted messengers embedded in their communities who bridge gaps in access to care, address misinformation, and promote health through culturally tailored education and outreach. The Fundamentals of Health Research training program was launched to address the gap in research engagement, and to support CHW/Ps’ professional development. This innovative initiative equips CHW/Ps with foundational knowledge about clinical research and the skills to apply that knowledge by engaging their communities in meaningful discussions about research and the importance of participation in research.MethodsThis 12-h, five-part training was developed collaboratively and delivered by experienced CHW/Ps. The curriculum included interactive components such as role-playing, IRB simulations, and the design of community-relevant research projects. The program was evaluated using a mixed-methods approach, including pre- and post-training surveys, satisfaction surveys, and 3- and 12-month follow-ups.ResultsBetween March and September 2023, 128 CHW/Ps completed the training; 103 (80.5%) completed the 12-month follow-up. Most participants identified as Latino/Hispanic (93%) and female (96%). Quantitative findings assessed knowledge gain (46.8% increase), attitudes toward research (49.1% reported an increased likelihood of research participation post-training), self-efficacy in research communication (overall average of 8 out of 10), and application of training in community settings (53.9% reported referring people directly to research studies). Qualitative findings highlighted increased understanding of research ethics, community impact, the importance of participation in research, and persistent barriers to participation such as mistrust and misinformation.ConclusionThe Fundamentals of Health Research training program is an innovative, scalable community engaged model for bridging the gap between research institutions and communities. Sustained support for community-driven, evidence-based training is essential to building capacity in the CHW/P workforce, which can help to advance research access, increase participation across populations, and improve health.